Heat loss recovery system of mobile compressor unit based on absorption refrigerating machine - V. L. Yusha; G. I. Chernov; D. V. Rubtsov; S. L. Terentjev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper considers the heat loss recovery system of a compressor unit based on the absorptionrefrigerating machine. The calculation of energy savings for driving the compressor based on the use of the mentioned system is performed. The energy saving amount is shown to be 14,86%. The parametric analysis is conducted of the dependence of the power consumed by the compressor on the solution pressure after the pump, the refrigerant solution concentration and mass flow rate fraction of the phlegm returned to the generator from the dephlegmator